New Trends in Bio-Based Aerogels - Loredana Elena Nita; Alina Ghilan; Alina Gabriela Rusu; Iordana Neamtu; Aurica P. Chiriac (Pharmaceutics, 2020)
(1) Background: The fascinating properties of currently synthesized aerogels associated with the flexible approach of sol-gel chemistry play an important role in the emergence of special biomedical applications. Although it is increasingly known and mentioned, the potential of aerogels in the medical field is not sufficiently explored. Interest in aerogels has increased greatly in recent decades due to their special properties, such as high surface area, excellent thermal and acoustic properties, low density and thermal conductivity, high porosity, flame resistance and humidity, and low refractive index and dielectric constant. On the other hand, high manufacturing costs and poor mechanical strength limit the growth of the market. (2) Results: In this paper, we analyze more than 180 articles from recent literature studies focused on the dynamics of aerogels research to summarize the technologies used in manufacturing and the properties of materials based on natural polymers from renewable sources. Biomedical applications of these bio-based materials are also introduced. (3) Conclusions: Due to their complementary functionalities (bioactivity, biocompatibility, biodegradability, and unique chemistry), bio-based materials provide a vast capability for utilization in the field of interdisciplinary and multidisciplinary scientific research.